2011
DOI: 10.1007/s13142-011-0084-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of pain and hypnosis for chronic pain

Abstract: In the past decade there has been a dramatic increase in (1) understanding the neurophysiological components of the pain experiences, (2) randomized clinical trials testing the efficacy of hypnotic treatments on chronic pain, and (3) laboratory research examining the effects of hypnosis on the neurophysiological processes implicated in pain. Work done in these areas has not only demonstrated the efficacy of hypnosis for treating chronic pain but is beginning to shed light on neurophysiological processes that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
0
20
0
2
Order By: Relevance
“…Of the five individual interventions that were ranked lowest on perceived efficacy, magnets, aromatherapy, herbal medicine, and Reiki lack evidence-based support for their use (Gagnier et al 2007; Pittler et al 2007; Lee et al 2008; Lee et al 2012). In contrast, hypnosis has demonstrated efficacy in treating chronic pain in non-addicted patients (Patterson and Jensen 2003; Dillworth et al 2012). Overall, counselors rated several interventions, which were not specified in the 2007 clinical practice guidelines, high in perceived efficacy and willingness to refer.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five individual interventions that were ranked lowest on perceived efficacy, magnets, aromatherapy, herbal medicine, and Reiki lack evidence-based support for their use (Gagnier et al 2007; Pittler et al 2007; Lee et al 2008; Lee et al 2012). In contrast, hypnosis has demonstrated efficacy in treating chronic pain in non-addicted patients (Patterson and Jensen 2003; Dillworth et al 2012). Overall, counselors rated several interventions, which were not specified in the 2007 clinical practice guidelines, high in perceived efficacy and willingness to refer.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the use of hypnosis in chronic pain, it was suggested that the responses to hypnosis were very variable, and that the available evidence suggests that hypnosis reduces daily pain and benefits other pain-related conditions. It was noted that hypnosis had synergistic effects with other psychological and physical treatments, and that further studies were needed to understand the mechanism of hypnotic analgesia and to create experimental bases to make hypnotic treatments more effective (32).…”
Section: Hypnosismentioning
confidence: 99%
“…Por su parte, la experiencia dolorosa se asocia con el incremento de la actividad simpática y un decremento de la actividad parasimpática. Para regular la actividad autonómica asociada al dolor se han desarrollado, aplicado y adaptado diversas intervenciones psicofisiológicas como la expresión emocional escrita (Pennebaker, 1997), las técnicas de relajación (Skinner, Wilson & Turk, 2012;Jensen & Turk, 2014) o la analgesia hipnótica (AH) (Dillworth, Mendoza & Jensen, 2011;Skinner, Wilson & Turk, 2012;Jensen & Turk, 2014).…”
Section: Autoría Y Derechos De Propiedad Intelectualunclassified